Interleukin 1 pretreatment decreases ischemia/reperfusion injury. - James M. Brown; Carl W. White; Lance S. Terada; Michael Grosso; Paul F. Shanley; D. Mulvin; Anirban Banerjee; Gary J. Whitman; Alden H. Harken; John E. Repine (1990)
Hearts isolated from rats treated 36 hr before with interleukin 1 (IL-1) had increased glucose-6-phosphate dehydrogenase (G6PD) activity and decreased hydrogen peroxide levels and injury after global ischemia (I, 20 min)/reperfusion (R, 40 min) compared with hearts from untreated rats. Hearts isolated from rats treated 6 hr earlier with IL-1 also had increased polymorphonuclear leukocytes (PMN), H2O2 levels, and oxidized glutathione (GSSG) contents compared with hearts from untreated rats. Depletion of circulating blood PMN by prior treatment with vinblastine prevented both early (from treatment 6 hr before study) IL-1-induced increases in myocardial PMN accumulation, H2O2 levels, and GSSG contents and late (from treatment 36 hr before study) increases in myocardial G6PD activity and protection against I/R. Our results indicate that IL-1 pretreatment causes an early (6 hr after IL-1 treatment) myocardial PMN accumulation and most likely an H2O2-dependent oxidative stress, which contributes to late (36 hr after IL-1 treatment) increases in myocardial G6PD activity and decreases in I/R injury.